Monoclonal antibody sequence assessment using a hybrid quadrupole-Orbitrap mass spectrometer. Issue 25 (15th June 2018) - Farrell, Amy; Carillo, Sara; Scheffler, Kai; Cook, Ken; Bones, Jonathan
Abstract : A multi-faceted method to verify anti-IL8 monoclonal antibody protein sequence using hybrid Orbitrap mass spectrometer. Abstract : Primary sequence determination is a key component in the development and characterisation of biotherapeutic drug substances. Although frequently performed using peptide mapping experiments, complementary methods are necessary to confirm full sequence identification. The requirement for a multi-faceted approach to sequence verification, ensuring single amino acid variations in the primary sequence are not overlooked, is highlighted in the data presented herein. A combination of liquid chromatography-mass spectrometry (LC-MS) strategies, including bottom-up peptide mapping, middle-up mass analysis of monoclonal antibody (mAb) IdeS digested subunits and intact protein analysis, were used to assess primary sequence for anti-interleukin 8 IgG1, a recombinantly expressed mAb from Chinese hamster ovary cells. This structured approach to primary sequence evaluation provides a framework for the evaluation of mAbs and biosimilar candidates and accentuates the importance of incorporating multiple analytical methods for therapeutic protein characterisation.